2013
DOI: 10.2147/clep.s48411
|View full text |Cite
|
Sign up to set email alerts
|

Data quality in the Danish National Acute Leukemia Registry: a hematological data resource

Abstract: BackgroundThe Danish National Acute Leukemia Registry (DNLR) has documented coverage of above 98.5%. Less is known about the quality of the recorded data.ObjectiveTo describe the present coverage of the DNLR, its completeness, and accuracy of individual variables for acute myeloid leukemia (AML). Furthermore, as a second measure of true coverage of the DNLR, to estimate AML incidence in Denmark from DNLR data and compare it to incidence reported from other AML registries.Patients and methodsBy the end of Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 22 publications
4
55
0
1
Order By: Relevance
“…Second, optimal registry design using standardized data is critical to maximize data quality. Our missing data rate is similar to other large observational registries [29, 30]. Although the use of a protocol with required tests would minimize missing data, we caution against mandating these practices for an observational pediatric registry, as this may decrease the rate of enrollment [31].…”
Section: Discussionsupporting
confidence: 61%
“…Second, optimal registry design using standardized data is critical to maximize data quality. Our missing data rate is similar to other large observational registries [29, 30]. Although the use of a protocol with required tests would minimize missing data, we caution against mandating these practices for an observational pediatric registry, as this may decrease the rate of enrollment [31].…”
Section: Discussionsupporting
confidence: 61%
“…We recently performed a validation study of the quality of AML registrations in the DNLR 8. In that study, the coverage of the DNLR was found to be 99.6% (95% confidence interval [CI] 99.3–99.8) with the DNRP used as a reference.…”
Section: Main Variablesmentioning
confidence: 99%
“… Note: Adapted with permission of Dove Medical Press Ltd., from Data quality in the Danish National Acute Leukemia Registry: a hematological data resource, Østgård L, Nørgaard J, Severinsen M, et al, Clin Epidemiol , 2013;5:335–344,8 Copyright © 2009; permission conveyed through Copyright Clearance Center, Inc. Abbreviations: AML, acute myeloid leukemia; ALL, acute lymphoblastic leukemia; CPR, civil registration number; ICD, International Classification of Diseases; FISH, fluorescence in situ hybridization; WHO, World Health Organization; WHO PS, World Health Organization performance status score; Y, yes; N, no; FAB, French-American-British.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[3], но ниже, чем в странах Европы и США (3,4-5,4/100 тыс.) [1][2]13]. Если принять во внимание, что данные в нашем исследовании собраны ретроспек-тивно и ограничивались муниципальными медицински-ми учреждениями, то очевидно, что реальная заболевае-мость по Москве выше 2,9/100 тыс.…”
Section: терапевтический архив 7 2015unclassified